Study on Drug Usage, Storage and Wastage among Households in Chengalpattu, Tamil Nadu, India - A Cross-Sectional Study - Nancy L,; M, Palanivel Sundaram; Logaraj M,; Anantharaman VV,; Kalaivanan R, (National Journal of Community Medicine, 2025)
Background: Improper drug storage is immensely prevalent in households. A significant number of families do not follow prescribed practices for maintaining the safety and efficacy of medications. Increased rates of unintentional poisoning, decreased drug efficacy, and the emergence of antibiotic resistance are just a few adverse consequences that might result from such negligence. Methodology: A total of 213 households were selected using multi-stage random sampling techniques. A pretested structured questionnaire on drug storage, usage, wastage in the households was used and detailed interview was conducted with the participants. Results: Majority of the participants 56.3% (120) belonged to the age group of 30- 40 years, most of the participants are graduates 39.4% (83). The prevalence of self-medication was 30.5%. Safe storage conditions with appropriate packing were used by 81.5% (167) of people. About 69.9% (149) has good knowledge on correct dosage of medications.91.2% (187) of households discard unused medications in the garbage. Commonly stored medicine was analgesics and antipyretics 21.6% (86). In this study Increasing age, Education and Family with senior citizens above 60 years have a strong association with storage condition of medicines at home. Conclusions: This study shows 96.3% prevalence of in-home storage medication practices. Ensuring the efficacy, safety, and cost-effectiveness of medications requires proper management from storage to use and waste prevention.